How do teacher support trajectories influence primary and lower-secondary school students’ study well-being - Ulmanen, Sanna; Rautanen, Pihla; Soini, Tiina; Pietarinen, Janne; Pyhältö, Kirsi (Frontiers in Psychology, 2023)
Effective long term teacher support is key to promoting and sustaining students’ study well-being at school. However, little is known about individual variations in the development of perceived teacher support and how such variations are associated with study engagement and study-related burnout. Also, understanding of the differences between age cohorts across school levels is still limited. To address this limitation, we used latent growth mixture (LGM) modeling to study whether teacher support trajectories influenced study engagement and study-related burnout among Finnish primary and lower-secondary school students. Two cohorts of students, namely primary school students from the 4th to 6th grades (N = 2,204) and lower-secondary school students from the 7th to 9th grades (N = 1,411), were followed for three years. LGM revealed four latent trajectories for teacher support, which were labeled high stable (72%), low stable (12%), decreasing (11%) and increasing (5%). The teacher support trajectories were strongly associated with students’ study engagement and study burnout. Moreover, heightened study-related burnout symptoms and decreased study engagement were associated with a decline in perceived teacher support, while higher levels of study engagement and low levels of study burnout symptoms were associated with a continuum of positive teacher support experience. Primary school students were more likely to employ stable and high levels of teacher support, compared with lower-secondary school students, highlighting the importance of improving conditions in lower-secondary school so that the teacher support will better reach all their students.